EFFECT OF JOB SATISFACTION, COMMUNICATION, AND DISCIPLINE ON EMPLOYEE ACHIEVEMENT - Andro Sinurat; Nelly Rosfita Sianipar; Theresya Aginta Ginting; Rosmaeni Waruwu; Melkyory Andronicus (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
This study was conducted to determine the effect of job satisfaction, communication, discipline on employee performance at PT Sinar Clear Suksesindo Medan. The population in this study are employees of the company. The method used in this study uses a quantitative approach. The population in this study was 120 people. The sampling technique using the Slovin formula with a sample of 92 respondents used in this study. The results obtained using a partial secsra obtained the value of job satisfaction tcount of 1.676 < ttable 1, 1.98729 So it can be concluded that job satisfaction has no effect and does not significantly increase employee performance. Communication has a tcount of 1.765 < ttable 1.98729, which means that communication has no effect and is significant on employee performance. Discipline has a tcount of 0.574 < ttable 1.98729, which means that discipline has no effect and is significant on employee performance. Meanwhile, simultaneously Fcount 9.439 > ftable 2.708 with a significance of 0.000 <0.05. This means that independent job satisfaction, communication and work discipline do not simultaneously affect the dependent, namely the work performance of employees at PT. Sinar Clear Suksesindo Medan.